2020
DOI: 10.1007/s10072-020-04775-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on stroke admissions, treatments, and outcomes at a comprehensive stroke centre in the United Kingdom

Abstract: Introduction The coronavirus disease (COVID-19) pandemic has changed routine clinical practice worldwide with major impacts on the provision of care and treatment for stroke patients. Methods This retrospective observational study included all patients admitted to the Royal Stoke University Hospital in Stoke-on-Trent, UK, with a stroke or transient ischaemic attack between March 15th and April 14th, 2020 (COVID). Patient demographics, characteristics of the stroke, treatment details and logistics were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 14 publications
7
37
1
2
Order By: Relevance
“…This could probably explain the longer delay in symptom onset-to-door time and onset to needle time in stroke patients and consequently the reduced proportion of patients who presented within the therapeutic time window for thrombolysis during the COVID pandemic. Interestingly, we did not observe any significant delay to reperfusion (door-to-needle and groin-to-puncture time) for IVT and EVT, in line with other centers worldwide ( 11 , 13 , 22 , 27 , 30 32 ) and with our preliminary report ( 47 ). By contrast Meza et al ( 6 ) and Briard et al ( 7 ) reported an increment in their door-to-needle time likely secondary to their new in-hospital infection control measures to manage stroke patients with suspected COVID-19 that may have delayed the acute stroke management.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could probably explain the longer delay in symptom onset-to-door time and onset to needle time in stroke patients and consequently the reduced proportion of patients who presented within the therapeutic time window for thrombolysis during the COVID pandemic. Interestingly, we did not observe any significant delay to reperfusion (door-to-needle and groin-to-puncture time) for IVT and EVT, in line with other centers worldwide ( 11 , 13 , 22 , 27 , 30 32 ) and with our preliminary report ( 47 ). By contrast Meza et al ( 6 ) and Briard et al ( 7 ) reported an increment in their door-to-needle time likely secondary to their new in-hospital infection control measures to manage stroke patients with suspected COVID-19 that may have delayed the acute stroke management.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our study showed that the proportion of patients with previous history of dementia, admitted to our HASU or assessed in our rapid outpatient TIA clinic, was statistically significantly lower during the COVID-19 outbreak compared to the same period in 2019. Several centers have described significant difference in severity at presentation of stroke patients but to date no difference in the degree of pre-stroke disability or dependence in the daily activities has been reported ( 11 , 30 , 32 ). Based on the available data, poor pre-admission functional status and dementia are risk factors for in-hospital mortality in patients with COVID-19 ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be that it is simply not safe for SLTs to deliver care to these groups in the COVID-19 context ( 39 ), or these patient groups may be less able to rapidly adapt or adhere to tele-therapy ( 40 ), leading to less engagement in this period. However, the reduction observed in stroke cases from SLTs is in line with other reports showing a concerning reduction in stroke admissions across the UK throughout the lockdown period ( 41 ). Similarly, the data shows a reduction in episodes of care for dementia patients, but relatively consistent representation of patients with Motor Neuron Disease (Amyotrophic Lateral Sclerosis), Parkinson's disease and those with brain tumors.…”
Section: Discussionsupporting
confidence: 91%
“…Many stroke centres have reported that COVID-19 discourages patients from contacting the health care system with an increase in prehospital delay and decrease in stroke admissions as a result [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. We have previously reported a decrease of almost 1/3 in stroke admissions in relation to the lockdown in Norway [6].…”
Section: Introductionmentioning
confidence: 69%
“…On the contrary, health authorities emphasised that suspected stroke victims should continue to seek medical attention and call the emergency medical services despite the lockdown. There are contradicting results regarding prehospital delay and the overall number and proportion of ischemic stroke patients receiving intravenous thrombolysis during the lockdown [1,2,5,7,8,[10][11][12][13] and reduced standard of care and delayed stroke care pathways with increased door-to-needle time have also been reported [1,2,5,7,8,[10][11][12][13]. The proportion receiving thrombolysis if they reached our hospital within the time window was similar for all three periods, indicating that the hospital's acute stroke workflow and pathway were not affected to a degree harming patients [10,20].…”
Section: Discussionmentioning
confidence: 92%